NDH-1 Is Important for Photosystem I Function of Synechocystis sp. Strain PCC 6803 under Environmental Stress Conditions - Zhao, Jiaohong; Gao, Fudan; Fan, Da-Yong; Chow, Wah Soon; Ma, Weimin (Frontiers in Plant Science, 2018)
Cyanobacterial NDH-1 interacts with photosystem I (PSI) to form an NDH-1-PSI supercomplex. Here, we observed that absence of NDH-1 had little, if any, effect on the functional fractions of PSI under growth conditions, but significantly reduced the functional fractions of PSI when cells of Synechocystis sp. strain PCC 6803 were moved to conditions of multiple stresses. The significant reduction in NDH-1-dependent functional fraction of PSI was initiated after PSII activity was impaired. This finding is consistent with our observation that the functional fraction of PSI under growth conditions was rapidly and significantly decreased with increasing concentrations of DCMU, which rapidly and significantly suppressed PSII activity by blocking the transfer of electrons from QA to QB in the PSII reaction center. Furthermore, absence of NDH-1 resulted in the PSI limitation at the functionality of PSI itself but not its donor-side and acceptor-side under conditions of multiple stresses. This was supported by the result of a significant destabilization of the PSI complex in the absence of NDH-1 but the presence of multiple stresses. Based on the above results, we propose that NDH-1 is important for PSI function of Synechocystis sp. strain PCC 6803 mainly via maintaining stabilization of PSI under conditions of environmental stresses.